Enterprise architecture assessment and user satisfaction model estimate in statistical organizations of African countries - Nhabomba, A.; Alturas, B.; Machado Alexandre, I. (The Electronic Journal of Information Systems in Developing Countries, 2025)
The objective of this study is to assess the current state of enterprise architecture (EA) and estimate the user satisfaction model (USM) in Statistical Organizations of African Countries (SOACs). The following inferential statistical techniques were used: hypothesis tests, principal components analysis (PCA), and multiple linear regression, to perform data analysis based on the judgments and opinions of the managers and Information Technology (IT) staff of SOACs. The study is based on several variables related to the performance and support of Information Systems and Technology (IST) in SOACs. The results confirmed the high complexity of IST in SOACs, which is further aggravated by the cyclical nature of statistical surveys and, for this reason, the poor integration and reuse of technological solutions associated with the absence of a formal EA. The results also led us to the conclusion that, as noted in general, in SOACs, user satisfaction is also positively influenced by IST when it is active, available, and reliable. An EA built from scratch will ensure optimized IST implementations, reducing common constraints and increasing the chances of getting real value from IST resources.